Nanoscale piezoelectric patches preserve electrical integrity of infarcted hearts - Luís M. Monteiro; Pedro J. Gouveia; Francisco Vasques-Nóvoa; Susana Rosa; Ifigeneia Bardi; Rita N. Gomes; Simão Correia-Santos; Leonardo Ricotti; Lorenzo Vannozzi; Daniele Guarnera; Liliana Costa; André M. Leite-Moreira; et al. (Materials Today Bio)
Ischemic heart disease is the leading cause of death worldwide. Several approaches have been explored to restore cardiac function, however few investigated new strategies to improve electrical functional recovery. Herein, we have investigated the impact of piezoelectric patches (Piezo patches), capable of generating electric charges upon mechanical deformation, on rat cardiac slices, healthy and ischemic hearts (ex vivo), on infarcted mice (in vivo) and on healthy and infarcted pigs (in vivo). Piezo patches did not preclude cardiac slice contractility, while compared with electrically inert control patches. In addition, Piezo patches showed an adequate safety profile in a working heart model as no electrophysiologic alterations were detected in healthy hearts. Epicardial implantation of Piezo patches in acutely infarcted mice hearts significantly improved myocardial electrical integrity without disturbing systolic function. Moreover, Piezo patches partially prevented ischemia-related adverse cardiac remodeling, reducing left ventricular chamber dilatation and compensatory hypertrophy. Coherently, Piezo patch-implanted hearts revealed downregulation of genes associated with extracellular matrix remodeling. Importantly, in vivo implantation of Piezo patches in porcine hearts revealed to be electrically safe as no major effects in its electrophysiology were detected. Overall, the results presented here endorse Piezo patches as a promising therapeutic strategy to improve post-myocardial infarction structural and electrical remodeling.